Iranian languages and scripts (2009)
This article aims to investigate the Iranian languages and their changes down through history, especially the Persian language or Farsi. In addition to the languages, Persian scripts and their development have been studied. Meanwhile, Persian literature with its glorious and famous poets, who composed excellent and brilliant poems in different periods, has been examined. Iran as a vast territory has had many different changes during history such as different languages, scripts, nations and cultures; therefore, studying these aspects is of great importance and interest. Due to the fact that many people and nations love the Persian language and its literature, they are eager to become acquainted with it and are interested in knowing how this language has influenced and affected the neighboring countries and other cultures.